2012
DOI: 10.1073/pnas.1214804110
|View full text |Cite
|
Sign up to set email alerts
|

Blink-related momentary activation of the default mode network while viewing videos

Abstract: It remains unknown why we generate spontaneous eyeblinks every few seconds, more often than necessary for ocular lubrication. Because eyeblinks tend to occur at implicit breakpoints while viewing videos, we hypothesized that eyeblinks are actively involved in the release of attention. We show that while viewing videos, cortical activity momentarily decreases in the dorsal attention network after blink onset but increases in the default-mode network implicated in internal processing. In contrast, physical black… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
143
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(165 citation statements)
references
References 27 publications
13
143
2
Order By: Relevance
“…In addition, the majority of large saccades were accompanied by a blink, as opposed to the small amplitude eye movements found at the lowest levels of complexity, many of which occurred without an associated blink. These findings are in agreement with previous publications [20][21][22] and may give support to the hypothesis that blinking, when associated with large gaze shifts, may help in reorganizing attentional resources by momentarily suppressing attention and transferring it to a different region of the visual stimulus. Recent psychophysics studies investigating perceptual switching when viewing a Necker cube 23 reach a similar conclusion.…”
Section: Discussionsupporting
confidence: 83%
“…In addition, the majority of large saccades were accompanied by a blink, as opposed to the small amplitude eye movements found at the lowest levels of complexity, many of which occurred without an associated blink. These findings are in agreement with previous publications [20][21][22] and may give support to the hypothesis that blinking, when associated with large gaze shifts, may help in reorganizing attentional resources by momentarily suppressing attention and transferring it to a different region of the visual stimulus. Recent psychophysics studies investigating perceptual switching when viewing a Necker cube 23 reach a similar conclusion.…”
Section: Discussionsupporting
confidence: 83%
“…Stern et al (1984) reported that eye blinking could serve as a physiological indicator of psychological processing, including expectancy and attention. Nakano et al (2012) reported that, based on their study in which participants' eye blinking and brain activities were measured while they were watching a movie, eye blinking caused reduction of attention-related neural network activities. This result suggests that if there is a long time between the onset of action and eye blinking, attention is sustained for a long time accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…We usually generate spontaneous eyeblinks every few seconds, much more often than necessary for ocular lubrication. Some studies have pointed out that the timings of eyeblinks are related to attentional breaks (Nakano, Kato, Morito, Itoi, & Kitazawa, 2013). For example, when people read a sentence, their eyeblinks increase at the punctuation marks (Hall, 1945).…”
Section: Eyeblink Entrainment and Speaker-listener Coordinationmentioning
confidence: 99%